An analysis of health and safety communication and its impact on incident occurrence at Eskom: Eastern Cape operating unit. - Qwemeshe, Nomsa (Central University of Technology, 2022)
This research focused on the various techniques used to communicate workplace health and safety messages. It further fixated on the impact and barriers of inefficient health and safety communication on Eskom: Eastern Cape Operating Unit’s health and safety performance; as well as the common workplace health and safety injuries and incidents and the leading causes to the injuries and incidents. The current study followed a quantitative research approach, in which relevant data on health and safety incidents from 2015 to 2019 was collected from Systems, Applications and Products in data processing of Environmental Health and Safety (SAP EH&S). Furthermore, a survey was conducted through the distribution of a questionnaire to managers, supervisors, engineers, and operators. Task observations were also conducted while operators were performing their work. A total of 614 incidents were analysed where the results revealed motor vehicle accidents and hand injuries as the most prominent types of incidents occurring at Eskom: Eastern Cape Operating Unit. The results further showed that 86.5% of the incidents were motor vehicle accident occurred in the Mthatha Sector. Unsafe worker behaviour, such as non-adherence to the wearing of person protective equipment (PPE) and negligence were found as the most common causes of incidents. The results of the questionnaire distributed to 294 participants showed that participants agree that non-adherence to rules was the most common unsafe behaviour that led to the occurrence of incidents. Further, 50% of the participants agreed that the health and safety message communicated were unclear in their transmission. There is sufficient evidence indicating that communication strategies in the workplace need to be strengthened to ensure the reduction of potential hazards pertaining to health and safety performance and incident occurrence. There is a surge of workplace health and safety incidents due to unsafe worker behaviour, despite legislative interventions. Moreover, inadequate communication methods and language barriers have a negative impact on Eskom: Eastern Cape Operating Unit’s health and safety performance. Therefore, there is an urgent need for improved health and safety communication methods, using innovative systems.
Thesis (Master of Health Sciences: Environmental Health)--Central University of Technology, 2022
Keywords: Workplace health and safety; Communication; Eskom; Workplace injuries; Motor vehicle accidents; Unsafe worker behaviour; Communication strategies